Autism-specific maternal anti-fetal brain autoantibodies are associated with metabolic conditions - Krakowiak, Paula (Autism Res, 2016)
LAY ABSTRACT: Approximately 23% of mothers of children with autism spectrum disorder (ASD) produce specific patterns of antibodies to fetal brain tissue that have been detected in only 1% of mothers of typically developing children. However, it is unknown what causes these ASD-specific anti-fetal antibodies to be produced. We examined the relationship between ASD-specific anti-fetal antibodies and metabolic conditions during pregnancy in 227 mothers of 2–5 year old children with ASD, enrolled in the CHARGE (Childhood Autism Risk from Genetics and the Environment) Study, and who had blood samples measured for these anti-fetal brain antibodies after study enrollment. Metabolic conditions included diabetes, hypertensive disorders, and prepregnancy obesity or overweight. The presence of ASD-specific anti-fetal brain antibody patterns was more common among mothers diagnosed with diabetes, hypertensive disorders, or overweight during pregnancy compared to healthy mothers, but these differences did not reach statistical significance. In a subset of 145 mothers whose children exhibited severe ASD symptoms, those diagnosed with type 2 or gestational diabetes were nearly 3 times more likely to have ASD-specific anti-fetal antibodies compared to healthy mothers. Further, those diagnosed with gestational diabetes specifically were over 3 times more likely to have these anti-fetal brain antibodies. In this exploratory study, mothers whose children had severe ASD and who were diagnosed with diabetes were more likely to have anti-fetal brain autoantibodies 2–5 years later. SCIENTIFIC ABSTRACT: Approximately 23% of mothers of children with autism spectrum disorder (ASD) produce specific patterns of autoantibodies to fetal brain proteins that have been detected in only 1% of mothers of typically developing children. The biological mechanisms underlying the development of ASD-specific maternal autoantibodies are poorly understood. We sought to determine whether ASD-specific maternal autoantibodies identified postnatally were associated with metabolic conditions (MCs) during gestation. Participants were 227 mothers of 2–5 year old children with confirmed ASD, enrolled in CHARGE (Childhood Autism Risk from Genetics and the Environment) between January 2003 and April 2008, and from whom blood samples were collected and analyzed for anti-fetal brain autoantibodies (Ab+). MCs included diabetes, hypertensive disorders, and prepregnancy obesity or overweight, ascertained from medical records or structured telephone interviews. Log-linear regression models were performed to estimate prevalence ratios (PR) and 95% confidence intervals (CI) based on robust standard errors. Fifty-six (25%) mothers were Ab+. Ab+ prevalence was higher among mothers with diabetes, hypertensive disorders, or overweight compared to healthy mothers, but differences were not statistically significant. In a subset of 145 mothers whose children exhibited severe ASD (31 Ab+), those diagnosed with type 2 or gestational diabetes were 2.7-fold more likely to be Ab+ (95% CI 1.1, 6.6), controlling for delivery payer and smoking. Gestational diabetes specifically was associated with a 3.2-fold increased Ab+ prevalence (95% CI 1.2, 8.6). In this exploratory study, mothers whose children had severe ASD and who experienced diabetes were more likely to have anti-fetal brain autoantibodies 2–5 years later.